Impacts of land use, anthropogenic disturbance, and harvesting on an African medicinal liana - McGeoch, Lauren; Gordon, Ian; Schmitt, Johanna (Biological conservation, 2008)
African medicinal plant species are increasingly threatened by overexploitation and habitat loss, but little is known about the conservation status and ecology of many medicinal species. Mondia whitei (Apocynaceae, formerly Asclepiadaceae), a medicinal liana found in Sub-Saharan Africa, has been subject to intensive harvesting and habitat loss. We surveyed M. whitei in Kakamega Forest, the largest of three remnant Kenyan forests known to contain the species. In 174 100 m 2 plots, we quantified the status of M. whitei and investigated its relationships with land use, disturbance and harvesting. With average adult densities of 101 plants/ha, M. whitei is not locally rare in Kakamega. However, the absence of flowers and fruits, together with a spatial disconnect between adults and juveniles, suggests that sexual regeneration is patchy or infrequent. Comparing among habitat types, we found that plants were most abundant in regenerating indigenous forest managed by the Forest Department, which permits some extractive uses. Conversely, plants were largest in indigenous forest managed by the Kenya Wildlife Service, which prohibits extractive uses. Most anthropogenic disturbances were not associated with M. whitei, but plant occurrence and density were higher along paths used by livestock than along other types of paths. Larger individuals appeared to be preferentially harvested, but adult plants were more likely to occur in harvested plots than un-harvested plots. This work emphasizes that restrictions on disturbance and extractive use do not automatically promote medicinal plant conservation. Moreover, harvesting may have important genetic and demographic consequences that are overlooked by studies focused on numerical losses.